Pengaruh Edukasi Terhadap Tingkat Pengetahuan Dan Stres Pasien Pre Percutaneous Coronary Intervention (PCI) Di ICU Murni Teguh Memorial Hospital - Hasibuan, Josua Sunardi; Simanullang, Rostime Hermayerni (Indonesian Trust Nursing Journal, 2025)
One way to treat patients with heart disease is through percutaneous coronary intervention (PCI). Frequent problems in PCI patients include stress and a lack of knowledge about the procedure. Providing education is thought to increase knowledge and reduce stress. The aim of this study was to analyze the effect of education on the knowledge and stress levels of pre-PCI patients. This research method is an analytical study using a one group pre and post-test design approach without a control group with a quasi-experimental research design. The study was conducted in the ICU Room of Murni Teguh Memorial Hospital. The population was 64 patients and the sample was obtained as many as 39 people. Sampling was by accidental sampling. The data used were primary data and secondary data. Analysis was carried out univariately and bivariately using the Paired Sample T-Test. The results showed that the characteristics of Pre PCI patients in the ICU Room of Murni Teguh Memorial Hospital were aged 51-60 years (38.5%), female (61.5%), had secondary education (high school) (46.2%), and worked (59.1%). Education influenced the level of knowledge of Pre PCI patients in the ICU of Murni Teguh Memorial Hospital, with p-value = 0.000 <0.05 and tcount = -27.870 > ttable (1.686), and influenced stress with p-value = 0.000 < 0.05 and the calculated t value = 11.922 > ttable (1.686). The conclusion of the study is that education has an effect on the level of knowledge and stress of Pre PCI patients. It is recommended that nurses always provide education to Pre PCI patients who will undergo cardiac catheterization so that patient knowledge increases and stress levels decrease.